The influence of combination use of CYP450 inducers on the pharmacokinetics of voriconazole: a systematic review. (8th February 2017) - Li, T.‐y.; Liu, W.; Chen, K.; Liang, S.‐y.; Liu, F.
Summary: What is known and objectives: Voriconazole is a triazole antifungal agent and is extensively metabolized via cytochrome P450 (CYP450); therefore, special precautions need to be taken when co‐administered with a known CYP450 inducer, which may lead to treatment failure. The influence of some CYP450 inducers on the pharmacokinetics of voriconazole has been described in previous studies, but a systematic review was lacking. In this study, we carried out a systematic review to assess the influence of CYP450 inducers on the pharmacokinetic (PK) parameters of voriconazole. Methods: Pubmed, Embase, Cochrane Library, Clinicaltrials.gov and three Chinese databases (CNKI, CBM and WanFang) were searched through January 2016. Interventional and observational studies comparing the PK parameters of voriconazole used alone or with CYP450 inducers in healthy volunteers and patients were included. The outcomes included were the area under the plasma concentration–time curve (AUC), peak plasma concentrations ( C max ) and trough plasma concentrations ( C min ). The quality of the included studies was assessed using Cochrane's risk of bias tool, Newcastle–Ottawa Scale (NOS) and a modified risk of bias tool for pharmacokinetic before‐and‐after studies. Results and discussion: Sixteen studies were included in this review: three randomized controlled trials (RCTs), five single‐arm before–after studies (SBAs), six cohort studies and two case reports. All studies except case reports had moderate to high quality. Of the 11 inducers reviewed, efavirenz, ritonavir (chronic use), phenytoin, rifampin and rifabutin significantly decreased mean AUC and C max of voriconazole; St John's wort significantly decreased only mean AUC; rifampin, rifabutin, phenobarbital and carbamazepine significantly decreased mean C min . Etravirine and Ginkgo biloba did not reveal any such influence. The influence of glucocorticoids may depend on its type and dose. What is new and conclusions: To conclude, the combination use of high‐dose efavirenz, high‐dose ritonavir, St John's wort, rifampin, phenobarbital, or carbamazepine with voriconazole is contraindicated as instructed in the drug label. Low‐dose efavirenz, low‐dose ritonavir, rifabutin and phenytoin may be used together with voriconazole provided TDM and dose adjustment of voriconazole. Moreover, this study shows there is low risk of drug–drug interactions when voriconazole is co‐administered with etravirine or G. biloba ; however, whether the use of glucocorticoids has a clinically significant effect on voriconazole still requires more evidence. This study also highlights the lack of clinical studies and future high‐quality studies assessing the influence of CYP450 inducers on voriconazole. PK parameters and dosing optimization should be designed to provide a more definitive answer regarding the necessity of TDM and the recommendations for dose adjustment of voriconazole. Abstract : This is the first systematic review investigating the influence of CYP450 inducers on voriconazole PK parameters. The results provide the answers regarding the necessity of TDM and the recommendations for dose adjustment of voriconazole when using concomitantly with CYP450 inducers.